Ray, A. (Ed.). (2021). Empowering Midwives and Obstetric Nurses. London: IntechOpen - Omona, Kizito (International Journal of Studies in Nursing, 2021)
In order to equip practitioner midwives and nurses, I find ‘Empowering Midwives and Obstetric Nurses’ a book to be treasured. This is more especially when it comes to supporting learning and preparing readers for the challenges faced in contemporary healthcare. This book with 192pages and twelve chapters is a treasure.